2022
DOI: 10.1021/acs.bioconjchem.1c00510
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Anti-Cancer Provascular Therapy Using Ultrasound, Microbubbles, and Nitrite to Increase Radiotherapy Efficacy

Abstract: Hypoxia is an important mechanism of resistance to radiation therapy in many human malignancies including prostate cancer. It has been recently shown that ultrasound targeted microbubble cavitation (UTMC) can increase blood perfusion in skeletal muscle by triggering nitric oxide signaling. Interestingly, this effect was amplified with a sodium nitrite coinjection. Since sodium nitrite has been shown to synergize with radiotherapy (RT), we hypothesized that UTMC with a sodium nitrite coinjection could further r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In cancer therapy, the importance of microvascular blood perfusion is well recognized, as reduced tumor perfusion indicates tissue hypoxia within the tumor [10,21]. The bioavailability of chemotherapy drugs is also in uenced by tissue perfusion, and any alterations in tumor blood ow can signi cantly impact the drug response, whether it is radiation or chemotherapy [22,23]. CEUS is a blood-pool imaging technique in which the contrast agent remains con ned to the vascular bed without diffusing into the tumor tissue or interstitial spaces.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer therapy, the importance of microvascular blood perfusion is well recognized, as reduced tumor perfusion indicates tissue hypoxia within the tumor [10,21]. The bioavailability of chemotherapy drugs is also in uenced by tissue perfusion, and any alterations in tumor blood ow can signi cantly impact the drug response, whether it is radiation or chemotherapy [22,23]. CEUS is a blood-pool imaging technique in which the contrast agent remains con ned to the vascular bed without diffusing into the tumor tissue or interstitial spaces.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64] Studies have demonstrated that that US-targeted microbubble cavitation could effectively increase tumor hemoperfusion, alleviate tumor hypoxia, and enhance effectiveness of radiotherapy. [65] This enhancement is facilitated by purinergic signaling and the discharge of NO through the activation of endothelial nitric oxide synthase. [66] Given the widespread use of contrast US agents in clinic, this technology is expected to improve the effectiveness of other treatment modalities, such as chemotherapy and immunotherapy.…”
Section: Promoting Chemotherapy-induced Antitumor Immune Responsementioning
confidence: 99%
“…Half of cancer patients undergo radiation therapy to delay or cure the disease. Radiotherapy is the use of ionizing radiation to kill tumor cells, while the surrounding normal cells may also be damaged, so there are large side effects that can lead to adverse reactions in patients [13][14][15][16]. Moreover, radiotherapy can lead to short-term or long-term toxicity, where the long-term toxicity is irreversible and even gradually accumulates and increases, seriously affecting the health of patients.…”
Section: Introductionmentioning
confidence: 99%